Buyer-seller interaction in facility services: Emerging paradoxes in the outsourcing approach of Italian municipalities. Issue 2 (9th March 2015) - Guercini, Simone; Ranfagni, Silvia
Abstract : Purpose: – The purpose of this paper is to focus its attention on the analysis of buyer-seller interactions in facility services. In particular it proposes to investigate the interactions Italian municipalities develop with sellers involved in facility services outsourcing and to evaluate how scientific contributions on business service (filtered through Service Dominant Logic) are constitutive paradigms of the interactions investigated. Design/methodology/approach: – The investigation is based on 15 case studies of small and medium-sized municipalities that are built on in-depth interviews with technical staff who, together with the mayors, perform the role of facility managers. Results from case studies are triangulated with secondary data and observations emerging from focus groups. Findings: – The research reveals paradoxes in the outsourcing processes of business services implemented by the public organizations analyzed. From these paradoxes it derives that the outsourcing of facility services in Italian municipalities is associated more with transactions than with interactions (municipalities do not act as operant resources) and that the transactions activated do not necessary generate efficiency. Originality/value: – Normative rules together with contextual factors jeopardize the adaptation in public organizations of interaction approaches to business service resulting from service and industrial marketing. The value of the paper lies in the identification of paradoxes as synthetic expressions of the divergences between empirical results and specialized interaction approaches on business services. In the light of these divergences, the paper proposes a contextualized re-interpretation of Service Dominant Logic.